Ionic Strength Effect on Copper(II) Biosorption by Folium camelliae Biomass: Equilibrium Study and Dynamic Modelling in Membrane Reactor - Guo, Jun-Jing; Chen, Wen-Bin (Asian Journal of Chemistry, 2013)
The removal of heavy metals by adsorption using biomaterials has been widely reported in the literature. The biosorption of copper(II) by the Folium camelliae was investigated a function of initial lead concentration, biosorbent concentration,temperature and pH, contact time and temperature was carried out. The nature of the possible biosorbent and metal ion interactions was examined by the FTIR technique. Adsorption equilibrium was observed within 1 h. Adsorption equilibrium data were well described by Langmuir isotherm model. The maximum adsorption capacity was 75.20 mg g-1 at 318 K and pH 4.4. From the Dubinin-Radushkevich model, the mean free energy was calculated as 12.1-15.8 kJ mol-1 ranging from 285-318 K, indicating the adsorption was taken place by chemical ion-exchange. Thermodynamic parameters (DGº, DHº and DSº) were also evaluated. These parameters showed that the adsorption process was feasible, spontaneous and endothermic under studied conditions. Desorption experiments indicated that the fixed lead on the biomass was stable in common solutions except acid media. These results announced an excellent adsorption material and also strongly suggest us that tea plant must be kept away from lead pollution.